Implementing Cloud Design Patterns for AWS : Solutions and design ideas for solving system design problems, 2nd Edition /: Solutions and design ideas for solving system design problems, 2nd Edition. (2019) - Keery, Sean; Harber, Clive; Young, Marcus
No abstract available